Analysis Of Ship Main Engine Procurement Process In The Shipyard Industry Using Supply Chain Operation Reference Method (SCOR) (Case Study: PT XYZ) - Ariany, Zulfaidah; Yusim, Adi Kurniawan; Utomo, Budi; Tampubolon, Mikhael Fernandus (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2024)
As a sector playing a crucial role in ship construction and repair, the shipbuilding industry faces significant challenges in material procurement, where materials constitute 50-70% of the total project cost. One of the materials requiring paramount attention is the ship's main engine. Effective supply chain management is critical to enhancing efficiency and effectiveness in the procurement process of ship engines. However, supply chain performance measurement research, especially in ship engine procurement, still needs to be improved. Therefore, this study aims to identify relevant performance metrics, analyze critical performance indicators, and provide recommendations based on the SCOR (Supply et al.) framework to improve ship engine procurement. The research results present 24 metrics distributed into four performance attributes based on SCOR 12.0, with 22 selected metrics aligned with the company's context. Analysis using the AHP method indicates that the reliability attribute has the highest weight (0.296), with the metric "Percentage of procurement received on time as per request" being the top priority (weight 0.143). This study provides a holistic view of crucial aspects of the ship engine procurement supply chain, supporting companies in enhancing their performance in the procurement process.